THE EFFECT OF IMPORTS OF COFFEE AND NATURAL RUBBER COMMODITIES ON ECONOMIC GROWTH IN INDONESIA - Muhammad Ridha; Fanny Nailufar (Journal of Malikussaleh Public Economics, 2022)
This study aims to determine the Effect of Coffee Imports and Oil and Gas Natural Rubber Imports on Indonesia's Economic Growth. By using the type of data in this research, quantitative approach to time series data from 1990 to 2020 sourced from the statistical reports of the Indonesian Directorate General of Plantations, BI Statistics, and BPS Indonesia. The analytical tool used is Multiple Linear Regression. The results partially show that coffee imports have a positive effect on economic growth as well as imports of natural rubber have a positive and significant impact on Indonesia's economic growth. Simultaneous test results stated that imports of coffee and natural rubber had a positive and significant effect on Indonesia's GDP. The correlation value of 0.8757 means that the relationship between coffee imports and natural rubber imports on economic growth as measured by GDP has a very strong relationship because the value is almost close to positive one